Dampak Pengoperasian Kereta Api Bandara terhadap taksi konvensional di Yogyakarta International Airport - Gusti Wahyu Nugraha (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to determine the impact of airport trains on taxis at Yogyakarta International Airport and find out whether there are differences in the income of conventional taxis. This research was taken in March 2022 at Yogyakarta International Airport. In obtaining data the author uses quantitative methods with questionnaires. The data was obtained from the results of distributing questionnaires to 55 all taxi drivers at the airport. The data processing method used was validity test, reliability test, statistical descriptive test, and hypothesis testing which included independent sample t-test. The results show the mean value of 2.56 which means it is negative. Researchers tested the Independent t-test hypothesis to calculate the difference in the income of taxi drivers before and after the airport train. The result is a value of 0.000, the value is less than 0.05, this shows the impact of airport trains on the income of conventional taxis.